PENGARUH PENGGUNAAN MEDIA POP-UP BOOK TERHADAP MINAT BELAJAR IPA DI SEKOLAH DASAR - Mutaqin, Ejen Jenal; Nurjamaludin, Muhammad; Alfiyanti, Nia (caXra: Jurnal Pendidikan Sekolah Dasar, 2021)
This study aims to determine the effect of pop up book media on interest in learning science in fifth grade students of SDN 1 Cibunar. This type of research is quantitative research with an experimental approach. The population in this study were all students of class V, the researchers used a sample of two classes, namely class VA which amounted to 16 people as the experimental class and class VB which amounted to 16 people as the control group. The data analysis technique used normality test, homogeneity test and t test. The posttest results of class VA students who use pop-up book media who have the highest score with an average of 80.00 while class VB does not use pop-up book media. It can also be proven by the results of the t-test calculation, namely there is a lower positive value with a score of 2.578 and an upper positive value and has a value of 10.172 or a Sig(2-tailed) = 0.002. Because the bottom is positive and the top is positive or Sig. (2-tailed) = 0.002 < = 0.05, which means that there is a significant effect of pop-up book media on the interest in learning science for fifth grade students.